Blender and Unreal Engine Character Design and Behavior Programming for 3D Games - Dekkati, Sreekanth (ABC Journal of Advanced Research, 2020)
A software game is a program used for entertainment and severe purposes that can be applied to many fields such as education, business, and health care. These more severe uses can apply to a variety of domains. The software game development technique is distinct from traditional software development due to the multidisciplinary nature of the game development methods, which include elements such as sound, art, control systems, artificial intelligence (AI), and human factors. The fundamental software engineering principles allow game creation to achieve maintainability, flexibility, reduced time and expense, and improved design. This study's objectives are to (1) evaluate the current level of research on the process of game development software engineering and (2) draw attention to aspects of this process that require additional investigation by researchers. In the research, we utilized a methodology that consisted of a comprehensive literature evaluation based on widely recognized digital libraries. The production phase of the game development software engineering process life cycle has been the focus of most research published on the topic. The pre-production phase has followed this. In comparison, the amount of research focused on the post-production phase is far lower than that of the pre-production and production stages. According to this research, developing video games through software engineering has many facets that require more attention from researchers; this is especially true regarding the post-production phase.